The nuclear localization signal of monkeypox virus protein P2 orthologue is critical for inhibition of IRF3-mediated innate immunity - Pengtao Jiao; Jianing Ma; Yuna Zhao; Xiaoxiao Jia; Haoran Zhang; Wenhui Fan; Xiaojuan Jia; Xiaoyuan Bai; Yiqi Zhao; Yongxu Lu; He Zhang; Jiayin Guo; et al. (Emerging Microbes and Infections)
The Orthopoxvirus (OPXV) genus of the Poxviridae includes human pathogens variola virus (VARV), monkeypox virus (MPXV), vaccinia virus (VACV), and a number of zoonotic viruses. A number of Bcl-2-like proteins of VACV are involved in escaping the host innate immunity. However, little work has been devoted to the evolution and function of their orthologues in other OPXVs. Here, we found that MPXV protein P2, encoded by the P2L gene, and P2 orthologues from other OPXVs, such as VACV protein N2, localize to the nucleus and antagonize interferon (IFN) production. Exceptions to this were the truncated P2 orthologues in camelpox virus (CMLV) and taterapox virus (TATV) that lacked the nuclear localization signal (NLS). Mechanistically, the NLS of MPXV P2 interacted with karyopherin α-2 (KPNA2) to facilitate P2 nuclear translocation, and competitively inhibited KPNA2-mediated IRF3 nuclear translocation and downstream IFN production. Deletion of the NLS in P2 or orthologues significantly enhanced IRF3 nuclear translocation and innate immune responses, thereby reducing viral replication. Moreover, deletion of NLS from N2 in VACV attenuated viral replication and virulence in mice. These data demonstrate that the NLS-mediated translocation of P2 is critical for P2-induced inhibition of innate immunity. Our findings contribute to an in-depth understanding of the mechanisms of OPXV P2 orthologue in innate immune evasion.